Coronavirus Interplay With Lipid Rafts and Autophagy Unveils Promising Therapeutic Targets - Fecchi, Katia; Anticoli, Simona; Peruzzu, Daniela; Iessi, Elisabetta; Gagliardi, Maria Cristina; Matarrese, Paola; Ruggieri, Anna (Frontiers in Microbiology, 2020)
Coronaviruses are enveloped, single stranded, positive sense RNA viruses, which can infect a variety of animals as well as human hosts, causing enteric diseases and common cold, respectively. In humans the infection usually induces mild respiratory diseases but sometimes it could be responsible for a more severe respiratory syndrome. Nowadays, the appearance of a new, highly pathogenic and lethal coronavirus variant, responsible of an epidemic in China and now pandemic, represents a global problem for human health. Unfortunately, only limited approaches are available to treat coronaviruses infections and a vaccine against this new coronavirus variant is not yet available. Lipid rafts are small, highly dynamic plasma membrane microdomains enriched in cholesterol, glycosphingolipids and phospholipids. They play an important role in a variety of cellular functions, including cell signal transduction or regulation of autophagy and, because of their capacity to cluster several pathogen recognition receptors, they represent a port of cell entry for several microbes. Although recent data highlighted the importance of either lipid rafts or autophagy in the life cycle of coronaviruses, the exact biological mechanisms are not completely understood and several questions remain still unanswered. In this review, we briefly describe the characteristic of coronavirus infection and replication at cellular and molecular level. In particular, we will consider the involvement of lipid rafts and autophagy in coronavirus infection and replication. We also hint how the manipulation of lipid rafts and autophagy may represent a potential therapeutic target to be investigated for the treatment of coronavirus infections.